How Far is the Qualitative and Quantitative Divide More Imagined than Real? Philosophy and Traditions in Management Research - Alsoaery, Abdulrhman; Alshehri, Hessa; Abdullah, Halah (Advances in Social Sciences Research Journal, 2023)
This article represent the debate in the two main research approaches namely qualitative and quantitative. Qualitative and quantitative approaches have special roles in research studies in numerous disciplines. Despite the debate on the division between the two approaches, there are a series of advantages and disadvantages, though depending on the aims and objectives of researchers. However, there is intense and significant disagreement concerning both nature of data and philosophical assumptions. Researchers, for that reason, increasingly demonstrate interest in merging the two concepts, in order to reap the merits of each as can be noticed in the increase number of this integrated approach in the management research.